Proposed Business Strategy for Angkasa Pura 2 at Husein Sastranegara International Airport - Mapriharto, Reski; Paramarta, Riawan B (The Indonesian Journal of Business Administration, 2015)
Abstract. PT Angkasa Pura 2 (AP2) is operator in airport management and operation services in West Indonesia flight area with PT Angkasa Pura 1 (AP1) manages airport in East Indonesia flight area. In West Java AP 2 manages several airport which Soekarno-Hatta, Halim Perdanakusumah, and Husein Sastranegara. In Husein Sastranegara however AP 2 has limited authority because, Husein Sastranegara International Airport owned by Indonesia Air Force (TNI AU). By 2013, passengers growth in Husein Sastranegara are profitable opportunity that AP 2 should captured. This also capitalized by condition Bandung city as tourist destination and in the near future Indonesia will face ASEAN Open Sky policy, which great opportunity for Husein Sastranegara with its status as international airport. The formulation strategy beginning with analyzing external and internal environment involving several methods such as Political, Legal, Socio-Cultural and Technology (PEST) Analysis, Corporate culture, Corporate structure and Corporate resource that contain Value Chain Analysis. The result of internal and external analysis determined with SWOT Analysis to generate IFAS Analysis and EFAS Analysis, TOWS Matrix, and interpreted to the Grand Strategy Selection Matrix.According to the Grand Strategy Selection Matrix, PT AP2 indicated in growth quadrant which mean high internal (strength and weakness) factors but quite low for the external (opportunity and threat) factors. All in all Husein Sastranegara currently still attractive for business as an airport while has some difficulties, growth airline passenger in Bandung should take into consideration. Keyword: Angkasa Pura 2, passenger growth, Bandung, Husein SastranegaraÂ